Identification of factors for measuring impact of digital repository by factor analysis - CHATURVEDI, ANKITA; SRIVASTAVA, G K (The Indian Journal of Agricultural Sciences, 2020)
KRISHIKOSH (https://krishikosh.egranth.ac.in), a digital repository of M Sc and Ph D thesis/dissertations carried out at different agricultural universities in India, facilitates new ways of sharing institutional knowledge that is leading to new perceptions about research institutions and innovations. The present study was conducted to identify factors that define the impact of digital repository based on the perspectives of the user community. Twenty-two variables measuring e-governance performance selected from literature review are used in designing the questionnaire for conducting opinion survey of researchers using KRISHIKOSH from five agricultural universities in 2019. Factor Analysis performed on the respondents’ perception data has resulted in extraction of five factors explaining about 71% of variation in the data. These factors are characterized as efficiency, interactivity, transparency, reliability and feedback, explaining 44.7%, 9.8%, 6.6%, 4.9% and 4.8% of variation in data, respectively. Based on the variables’ loading coefficient in each extracted factor, the identified variables can be prioritized and focused for maximizing the impact of digital repository and similar e-governance projects in agriculture sector.